Kajian Molecular Docking Senyawa Karwinaphthol B dari Tanaman Bawang Dayak (Eleutherine palmifolia (L.) Merr) sebagai Inhibitor Enzim Glukokinase - Puji Astuty; Noer Komari (Jurnal Natural Scientiae, 2022)
Karwinaphthol B is a compound of the naphthoquinone group. Karwinaphthol B is a chemical compound found in Bawang Dayak. Karwinaphthol B is one of the compounds considered to have antidiabetic effects. Diabetes Mellitus is a chronic disease that occurs when the body cannot produce enough insulin or cannot use insulin (insulin resistance) which causes blood glucose levels to rise (hyperglycaemia) under normal conditions. This study aims to see the potential of karwinaphthol B as a glucokinase inhibitor with parameters such as ∆G value and interaction of amino acid residues with molecular docking and pharmacophore studies using filter Lipinski, pkCSM, and SwissADME. The results of molecular docking showed that karwinaphthol B compound had potential as antidiabetic based on the ∆G value of -8.39 kcal/mole. Karwinaphthol B compound has an LD50 value of 2.168 mole/kg which is included in the non-toxic category; does not have hepatotoxicity, skin sensitization, and has a good bioavailability value. The interaction of Karwinaphthol B compounds with glucokinase enzymes at amino acid residues VAL62, ARG63, SER64,THR65, PRO66,  GLU67, GLY68, SER69, GLN98, MET210 , ILE211, TYR214, TYR215, CYS220, GLU221, MET235,  CYS252, LEU451, VAL452, and VAL455.